LA ATENCIÓN DISPERSA EN EL APRENDIZAJE DE LAS MATEMÁTICAS DE LOS NIÑOS Y NIÑAS DEL CUARTO AÑO DE LA UNIDAD EDUCATIVA “SAN VICENTE DE PAÚL” RIOBAMBA PERIODO 2017 – 2018 - Castillo Robalino, Hernán Marcelo (2020)
The purpose of this research was to conduct children’s lack of atention and concentration during the teaching-lerning process. Among the objectives, we had to diagnose how widespread attention influences children’s learning. To indentify the causes for which it occurs and seek the solution to improve attention. The theoretical framework was about the attention, the influence of widespread attention on learning, as well as definitions, consequences, causes, and factors that affect widespread attention. Moreover, in the same way, Iwas able to analyze learning, types, styles the same ones that helped to develop my proyect and also what teachers should do to improve the students. The methodology was framed within the quantitative paradigm, it is descriptive, and it correspond to the so-called development projects that present an alternative solution to the problema. It supported by research: documentary, bibliographical, and field. The technique used was the survey and the interview, for wich the questionnaire and the survey elaborated considering variables and the research objectives. The study universo was made up of students in the fourth year of primary education and their teachers. The aim of this Project was to reduce the lack of attention and, at the same thime, to contribute to the improvement of the teaching-learning process.